Social inclusion as a therapeutic and educational factor in a music therapy setting - Loss, Felix (2016)
Inclusive approaches for children with special needs are applied in both the fields of music therapy and (music) education. In practice, inclusive music therapy groups consist only of children with special needs, whereas an inclusive kindergarten group for example may consist of typical and non-typical children, yet not in an actual therapy setting. Both practices hold explicit benefits for typical and non-typical children, however mutually exclusive of one another. The aim of the study is to explore the effects of social inclusion in a group consisting of typically and non-typically developing children within a music therapy setting. The focus lays on the therapeutic benefits for the special needs children and the educational benefits for the typical children. Furthermore, this study outlines the possibilities and limitations of the approach, and the possible implications for music therapy practice and in music education settings. Therefore, a group of three children, two typically developing girls and one boy diagnosed with Autism Spectrum Disorder (age between 4 and 7 years), received 18 music therapy sessions. Each session’s structure and activities were planned, evaluated, and reorganized through an action research paradigm. The process was videotaped and three of the sessions (beginning, middle-phase, end-phase), were analyzed using a mixed methods approach of quantitative content analysis and qualitative descriptive interpretation analysis. Additionally, interviews of the mothers were taken and were analyzed using qualitative content analysis. Preliminary results show that the therapy for the boy with autism may have enhanced active pro-social behavior within and outside the therapy sessions, as well as having increased the social skills of the typically developing girls. Furthermore, musical and social goals could be targeted in both therapeutic and educational ways.